MANAJEMEN PEMBIAYAAN PENDIDIKAN UNTUK MENDUKUNG KEBIJAKAN KEMANDIRIAN EKONOMI PONDOK PESANTREN DI KABUPATEN ACEH TENGGARA - Prasetyo, Muhammad Anggung Manumanoso (UIN Imam Bonjol Padang, 2019)
The subject of this research is how to manage pesantren in Southeast Aceh in the aspect of economic independence, that relates to the problem of financial management in pesantren. From 36 pesantren, only 6 of them are accredited A, one of the assessment indicators is economic aspect, it means the rest are considered not sufficiently financially independent. If we/YOU see the data that is processed is qualitative using field research. The data obtained from the managers of pesantren in Southeast Aceh. The method of data collection was done through observation, interview, and documentation techniques. The study uses observation guides, interview guidelines and data documentation as research instruments. Data processing and analysis technique were carried out through three stages; data reduction, data presentation and data verification. At the implementation level, generally the management of pesantren has held business units from various existing sources / potentials, in fact the implementation has not been running as it should. The study also found that there is a relationship between quality and accessibility on the one hand, and the composition of income and expenditure at the pesantren level on the other hand. Strategic advice for the development of financial management in pesantren in Southeast Aceh as well as research findings, including (1) the presence of a financial manager or someone who has financial competence; (2) having a development plan as a form of achieving targets; (3) forming business units as a form of independence; and finally (4) team cohesiveness.